Reduced mitochondrial respiration in peripheral T cells after paediatric heamatopoietic stem cell transplantation - Mølgaard, Kasper; Kielsen, Katrine; Ifversen, Marianne; Met, Özcan; Svane, Inge Marie; Müller, Klaus (Frontiers in Immunology, 2024)
Recovery and functional differentiation of T-cell subsets are central for the development of immune function and complications after allogeneic hematopoietic stem cell transplantation (HSCT), but little is known about the cellular respiration and factors influencing T-cell metabolic fitness during immune maturation after HSCT. We included 20 HSCT patients and analysed mitochondrial oxidative phosphorylation and mitochondrial fitness in peripheral blood mononuclear cell samples collected at days +90 and +180 after HSCT. Phenotypic analysis revealed lower overall T-cell counts, lower CD4+/CD8+ ratio and a skewed distribution of early T-cell subsets at day +90, gradually recovering by day +180. Although ATP turnover in HSCT patients was similar to healthy controls, the spare respiratory capacity (SRC) of T cells, reflecting the available energy reserve, was significantly reduced at day +90 and +180 compared to healthy controls. This reduction in SRC was not correlated with the occurrence of acute graft-versus-host disease (aGVHD), the intensity of conditioning regimens and markers of T-cell exhaustion. In conclusion, we found significantly depressed SRC until six months post-HSCT, but we were not able to identify transplant-related risk factors or associations with the clinical outcome.